THERMOTHERAPY IN HEMATOLOGIC RESPONSE AFTER RESISTANCE EXERCISE IN BODYBUILDERS (Fiep Bulletin - online, 2012)
Resistance exercise (RE) induce the inflammatory response and leukocytosis, however  the thermotherapy may decrease the effects of this response. The objectives of this study were to evaluate the changes caused by the ER and the effects of interventions thermotherapy on the concentrations of cells (white, red and platelets) and electrolytes (Na+, K+, Mg++ and Ca++) blood in trained volunteers. The sample was composed of twelve volunteers (26 ± 5years, BMI: 25 ±4kg/m2) bodybuilders for more than six months. The quadriceps muscle strength was evaluated by testing 10 repetition maximum (10RM) in the leg extension, squat and leg press. Were performed three exercise sessions at intervals of seven days, being a non-intervention (CONT), intervention with hypothermia (HIPO: 2 to 5°C) and hyperthermia (HIPER: 45 to 47°C). Thermotherapy was applied to the quadriceps muscle for 10 minutes. The blood collections were performed: baseline, after exercise and after the intervention. The ER induced an increase in all variables studied hematological and electrolytes Mg++ and Ca++, and the sessions (CONT vs HIPO vs HIPER) showed no differences. Control intervention in platelets, neutrophils, monocytes and K+ did not return to baseline. The ER promotes leukocytosis and electrolyte abnormalities, and the thermotherapy interventions favoring those hematological recoveries after these exercises.
Keywords: induced hypothermia; hyperthermia induced hematology.